I believe the answer is 24 times
hope this helps!
Answer:
7) (f+g)(x) = 4^x +5x -5
8) (f-g)(x) = 4^x +x +5
Step-by-step explanation:
7) add the two expressions.
(f+g)(x) = f(x) +g(x) = (4^x +3x) +(2x -5)
(f+g)(x) = 4^x +5x -5
__
8) subtract g(x) from f(x).
(f-g)(x) = f(x) -g(x) = (4^x +3x) -(2x -5) = 4^x +3x -2x +5
(f-g)(x) = 4^x +x +5
Answer:
(1,0)(-4,0)
Step-by-step explanation:
Answer:
22
Step-by-step explanation:
Points Y and X are are the midpoints of the segments HI and HG respectively.
Therefore,
By Mid-segment formula:
IG = 2*YX = 2* 11 = 22 units
Step-by-step explanation:
The area would be 9 times compared to the area of the original square. To test this, you can let the side of the original square be equal 1. By tripling this side, the side becomes three. Utilizing the area of a square formula, A= s^2, the area of the original square would be 1 after substituting 1 for s. Then, you do the same for the area of the tripled square. With the substitution, the area of the tripled square would be 9. This result displays the area of the tripled square being 9 times as large as the area of the original square. This pattern can be used for other measurements of the square such as:
let s = 2, Original Area= 2^2 = 4 Tripled Area= (2(3))^2 = 6^2= 36. 36/4 = 9
let s = 3, Original Area = 3^2 = 9 Tripled Area - (3(3))^2 = 9^2 =81. 81/9 = 9
let s = 4, Original Area = 4^2 = 16 Tripled Area - (4(3))^2 = 12^2 = 144. 144/16 = 9
let s = 5, Original Area = 5^2 = 25 Tripled Area - (5(3))^2 = 15^2 = 225. 225/25 = 9
let s = 6, Original Area = 6^2 = 36 Tripled Area - (6(3))^2 = 18^2 = 324. 324/36 = 9
let s = 7, Original Area = 7^2 = 49 Tripled Area - (7(3))^2 = 21^2 = 2,401. 2,401/49 = 9
You can continue to increase the length of the square and follow this pattern and it will be consistent.